IBN JINNIY WA JUHUDUH AL-LUGHAWIYYAH FĪ AL-KHAṢĀ’IS: DIRĀSAH WAṢFIYYAH TAḤLĪLIYYAH - Toni Pransiska (Universitas Islam Negeri Ar-Raniry, 2017)
Ibn Jinny (Mosul, 322-329 H) one of Arabic linguist was very multitalented and multidisciplinary master in Islamic scholarship. Through his masterpiece “Al- Khāshaish”, Ibnu Jinny tried to read discourse and discussion from the original Arabic linguistics that focused on the debate nahwu and fanaticism of his Mazhab into studies of a more generally and comprehensively. Language, according to Ibn Jinny, is not a purely rational entity but a social dimension, therefore, methods, theories and approaches were used also must necessarily incorporate both dimensions. If the linguistic theory of Modern West focused on object of studies to four important elements such as; Phonetics (‘Ilm al-Ashwāt), Morphology (Sharf), Syntax (Nahw) and Semantics (‘Ilm al-Dilālah), then the Arabic linguistic tradition - as Ibn Jinny’s study - has led Western Linguist studies. Even the sociological approach or another we can browse and look for the roots of the theories of Ibn Jinni and linguists generations thereafter.